ESTUDO DE EFICIÊNCIA ENERGÉTICA EM MODAL FERROVIÁRIO POR ANALISE TRADE-OFF UTILIZANDO CONCEITOS DE CUSTO TOTAL. - CARVALHO, Enniogleiser Pereira de (2018)
The mining industry uses a lot of modal rail transport because this is the best land modal to balance the relationship between heavy haul and operating costs. The most representative operating costs are related to fuel consumption. Based on the literature, was observed that studies related to the energy efficiency of the railway modal are much less frequent than in the modal road. Then, this work carried out a case study on the Carajás Railroad, the most heavily loaded railroad in Brazil, separated into 3 steps: Cost evaluation, capacity evaluation and trade-off analysis. In the evaluation of transport costs of the EFC, the fuel share was approximately 50%. Concepts of Deming cycle(PDCA) analysis was used to analyze the Energy Efficiency, was identified that the traction types had a significant influence on the results. the traction with 4 DC locomotives presents the best energy efficiency (1.408x10-3l.t-1.km-1). The optimum traction model was identified for better energy efficiency, providing a consumption reduction of approximately 216 liters of fuel per trip. Assuming the costs based on reports submitted to ANTT, the average annual costs per asset and fixed costs of operation per train. In the capacity analysis the travel times of the three usual traction configurations were studied. It was identified that the data showed high variability (18%), making it impossible to perform an effective comparative analysis between scenarios, since the lower power traction presented less travel time, which was not expected according to the theoretical analysis. Combining theoretical models of railway capacity sizing, was possible to evaluate the relation between travel time with quantity of necessary assets, one cycle hour corresponds to approximately 0.77 equivalent trains (3 or 4 Locomotives and 330 wagons). In the trade-off analysis, was observed that 45% of the initiatives had a relation between energy efficiency and transport capacity. Using the financial analysis methodology NPV (Net present value) applied to the concept of total cost, derived from integrated logistics, the financial feasibility of some scenarios relating to energy efficiency and travel cycle was evaluated. A NPV was estimated equivalent to the sensitivity analysis referring to the 1-hour increase in the travel cycle. Regarding the optimization of traction models, a potentially positive NPV was estimated to the best traction type. The application of trade-off analysis of logistical costs proved to be fundamental to take decision and ensure greater competitiveness of the railway modal.